Perancangan Impeller Dan Volute Pompa Sentrifugal Dengan Fluida Kerja Air Gambut - F, Simon Petrus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Pump is a machine that can be used to transporting of fluids from a low pressure to the high pressure. One of the kinds of pump is the centrifugal pump. The centrifugal pump is widely used to any purposes in any company. PDAM Tirta Siak is a company that produces clean water for people. PDAM in their distribution operation uses centrifugal pump. That centrifugal pump has some important component that is named as impeller.The impeller is a component of centrifugal pump that has most influence performance of centrifugal pumpsuch as the head. Design of impeller and volute of centrifugal pump is for handling a different fluid.Peat water has a different viscosity value to clean water. The viscosity cause a slip factor phenomenon. The slip factor decreases absolute velocity in tangential component, therefore this phenomena caused fluid out the pump with larger angle. Based on it, in this research we want to design the impeller that can handling peat water with viscosity as the center point.Keywords : Impeller, (Î²), Slip factor, Viscosity, Head, Volute.